2015
DOI: 10.1128/aem.00720-15
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal Bacterial Community Composition in Dairy Cows Is Dynamic over the Course of Two Lactations and Correlates with Feed Efficiency

Abstract: bFourteen Holstein cows of similar ages were monitored through their first two lactation cycles, during which ruminal solids and liquids, milk samples, production data, and feed consumption data were collected for each cow during early (76 to 82 days in milk [DIM]), middle (151 to 157 DIM), and late (251 to 257 DIM) lactation periods. The bacterial community of each ruminal sample was determined by sequencing the region from V6 to V8 of the 16S rRNA gene using 454 pyrosequencing. Gross feed efficiency (GFE) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
223
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(270 citation statements)
references
References 43 publications
33
223
3
Order By: Relevance
“…When looking at the intestinal microbiota, similar to previous findings in cattle, the overall intestinal bacterial diversity did not cluster by RFI rank, but rather, RFI-associated variations in community membership were detected (12,34). Interestingly, in our study, microbial diversity, as well as composition, was impacted by both age and intestinal site.…”
Section: Discussionsupporting
confidence: 71%
“…When looking at the intestinal microbiota, similar to previous findings in cattle, the overall intestinal bacterial diversity did not cluster by RFI rank, but rather, RFI-associated variations in community membership were detected (12,34). Interestingly, in our study, microbial diversity, as well as composition, was impacted by both age and intestinal site.…”
Section: Discussionsupporting
confidence: 71%
“…In a recent study involving 118 animals, two different possible low-methane communities were identified in sheep (9), meaning that there could be multiple underlying animal genotypes. Similar studies of dairy cows and steers with differential residual feed intake (RFI) suggest a correlation between RFI and certain rumen bacterial (10)(11)(12) and archaeal (13) taxa. However, due to the logistical and financial challenges of maintaining large dairy or beef research herds, the numbers of animals used in these studies were limited.…”
mentioning
confidence: 89%
“…In addition, rumen microbes can also synthesize most B vitamins to meet the nutritional demands of the host (4). To date, multiple studies have reported that the rumen microbial composition is associated with feed efficiency in beef (5-9) and dairy (10) cattle, suggesting that rumen microbial function is one of the factors that impact the cattle's feed efficiency. Feed efficiency is one of the most important traits in cattle farming because the feed cost accounts for most of the production expense, accounting for 60 to 70% of the total cost in beef production (11).…”
mentioning
confidence: 99%